Diurnal Variation in the Core Interthreshold Zone in Women and its Sex Difference - Kakitsuba Naoshi; B. Mekjavic Igor (International Physiology Journal, 2018)
Background: The core interthreshold zone (CIZ) is defined as the range between core temperature (Tc) at the onset of shivering and the Tc at the onset of sweating under consistent mean skin temperatures of 28°C to 30°C. A previous study demonstrated a diurnal change in the CIZ for male subjects and its relationship to the cutaneous sensation threshold zone (CSZ). In the present study, diurnal changes in the CIZ and the CSZ for young Japanese female subjects were investigated using the same experimental protocol from the study of male subjects and the sex differences in these responses were then examined. Methods: The CIZ and the CSZ were measured in 10 female subjects who participated in three experiments in a single day during the morning, afternoon, and evening in the summer of 2014 (single-day experiment), and six female subjects who participated in the same experiments on the morning of day 1, the afternoon of day 2, and the evening of day 3 during the summer of 2016 (multiple-day experiment). Air temperature was controlled at 25°C. Each subject wore a suit perfused with 25°C water at a rate of 600 cc/min, and exercised at 50% of their maximum work rate on an ergometer for 10–15 min until their sweating rate increased. They then remained seated, without exercising, until their oxygen uptake increased. Rectal temperature, skin temperature at seven sites, the forehead-sweating rate, and oxygen uptake were continuously monitored throughout the experiment. Cutaneous warm and cold sensation thresholds were measured at three sites using 1-cm2 and 2-cm2 probes. Results: The results from the single-day experiment demonstrated that the CIZ was proportional to core temperature prior to exercise (Tc-init) whereas the results from the multiple-day experiment demonstrated that the CIZ increased continuously from morning to evening despite almost a constant Tc-init. The CIZ appeared to be proportional to the CSZ measured with the 2-cm2 probe. When compared with the results from the previous study of men, no significant sex difference was observed between the CIZ of 0.25±0.07°C for female subjects and 0.21±0.05°C for male subjects. Conclusion: No significant sex difference or diurnal variation in the CIZ was confirmed. Continuous increase in the CIZ from morning until evening is expected in both men and women under a normal Tc circadian rhythm.
Keywords: thermoregulation